Exploring Students Reading Material Preferences: A Comprehensive Descriptive Analysis - Gandari, Meisy; Jaya, Sinarman (Journal of English Language and Education, 2024)
The study explores the preferences of students of English Language Education at Muhammadiyah University of Bengkulu in choosing reading materials. The research uses comprehensive descriptive analysis methods to understand the factors that influence student choices, focusing on interests, motivations, print format, and novel-like genres. The relationship between student reading preferences and reading ability is significant, as reading in line with student interests leads to increased interest and active participation in the learning process. The majority of students prefer printed reading materials for lectures, because they help them focus and understand reading without disturbance. However, some students prefer digital reading because of its ease and portability. The study highlighted the importance of understanding students' preferences in choosing reading materials to support the success of the learning process. The relationship between students' reading preferences and reading ability is important, because reading in line with students' interests ensures their active participation in the process of learning. A student should know the material and type of reading that is preferred, and based on the results of research the lecturer also plays an important role in knowing the preferences of students so that they can be a reference in choosing the reading material and combining on learning so that it fits the interests of students.